UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA DENGAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPA SD - Degi Alrinda Agustina (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2017)
This research aims to improve the science process skills of students Natural Sciences (IPA) using the model of Problem Based Learning. Science process skills isscientist behavioral that can be learned and developed by students through the learningprocess in the classroom. Science process skills provide more opportunities for studentsto play an active role in learning. This research uses a Classroom Action Research(PTK), which is composed of two cycles. Each cycle includes three stages: planning,action accompanied by observation, and reflection. The collection of data throughobservation, interviews, documentation and testing. The results showed that the use ofmodels Problem Based Learning in science teaching can improve science process skillsof students in the learning process. It is seen from the value of science process skills ofstudents has increased from cycle I to cycle II which show the percentage of students'science process skills by 64.17% in the first cycle to 78.96% in the second cycle. Keywords: a model problem based learning, science process skills, science learning